Assessing Science Learning Outcomes using Assessment Instruments Based on Higher Order Thinking Skills - Ni Made Mita Puspita Dewi; I Made Suarjana; Luh Putu Putrini Mahadewi (Universitas Pendidikan Ganesha, 2021)
There were still many teachers who had difficulty making student learning assessment instruments. The orientation of the learning carried out was still at the level of low-level thinking (remembering, memorizing, and understanding) so that students had low knowledge. This study aimed to develop an instrument for assessing science learning outcomes on Theme 8 based on Higher Order Thinking Skills. This type of research was development research. The model used in this study was 4D which is divided into four stages, namely Define, Design, Develop, and Disseminate. The techniques used in collecting data were observation, interviews, document recording, rating scales, and tests. The instrument used in collecting data was a questionnaire. The results of the study will be analyzed for validity, reliability, discriminating power, and level of difficulty, quality of distractors, practitioner responses, and student responses. Instruments designed to collect data were tested first to find out the instrument's validity. The results of the research were the analysis of the content validity test and the items were in very high criteria. Based on the results of the reliability test, the instrument being tested had a very high consistency. In the analysis of the quality of the distractor, the instrument functions well. In the analysis of practitioners' responses and student responses, the category was very good. It can be concluded that the instrument that assesses the science learning outcomes of theme 8 based on Higher Order Thinking Skills was valid and feasible to be used as an assessment instrument for students.